Doping effect on the physical properties of Ca10Pt3As8(Fe2As2)5 single crystals. (9th November 2017) - Pan, Jiayun; Karki, Amar; Plummer, E W; Jin, Rongying
Abstract: Ca10 Pt3 As8 (Fe2 As2 )5 is a unique parent compound for superconductivity, which consists of both semiconducting Pt3 As8 and metallic FeAs layers. We report the observation of superconductivity induced via chemical doping in either Ca site using rare-earth (RE) elements (RE  =  La, Gd) or Fe site using Pt. The interlayer distance and the normal-state physical properties of the doped system change correspondingly. The coupled changes include (1) superconducting transition temperature T c increases with increasing both doping concentration and interlayer distance, (2) our T c value is higher than previously reported maximum value for Pt doping in the Fe site, (3) both the normal-state in-plane resistivity and out-of-plane resistivity change from non-metallic to metallic behavior with increasing doping concentration and T c, and (4) the transverse in-plane magnetoresistance (MRab ) changes from linear-field dependence to quadratic behavior upon increasing T c . For La-doped compound with the highest T c (~35 K), upper critical fields ( H c 2 a b, H c 2 c ), coherence lengths ( ξ ab, ξ c ), and in-plane penetration depth ( λ ab ) are estimated. We discuss the relationship between chemical doping, interlayer distance, and physical properties in this system.